Investigation into the Cavally River ichthyofauna in Guinea - Soromou Lanan Wassy; Yacouba KONATE; Kpoulomou Lah; GOUMOU Pé 2; TEA Mama Agnès (African Scientific Journal, 2023)
In recent years, naturalists and scientists have been concerned about the ichthyological fauna of rivers and bodies of water. The aim of this study was to identify the fish species inhabiting the Cavally river. Based on consultation with the managers and analysis of the archives, it was established that fishing is practised in the area, but on a limited scale. Surveys of stakeholders revealed 8 families (including 14 genera) of fish, divided between the most abundant (Mormyrudae, Cyprinidae), the rarest (Polypteridae), the most threatened with extinction (Malapteridae) and those that have recently appeared (Claria gariepinus, Oreochromis niloticus and Heterotis niloticus). The fishing equipment used in the area includes fish hooks, nets and creels.